2009
DOI: 10.1111/j.1752-0606.2009.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Family Therapy Outcome With Alcohol‐Abusing, Runaway Adolescents

Abstract: Treatment evaluation for alcohol problem, runaway adolescents and their families is rare. This study recruited primary alcohol problem adolescents (N = 119) and their primary caretakers from two runaway shelters and assigned them to either: 1) home-based Ecologically-Based Family Therapy (EBFT), 2) office-based Functional Family Therapy (FFT), or 3) Service as Usual (SAU) through the shelter. Findings showed that both home-based EBFT and office-based FFT significantly reduced alcohol and drug use compared to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
193
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(213 citation statements)
references
References 70 publications
3
193
4
2
Order By: Relevance
“…In the first (Slesnick & Prestopnik, 2009) EBFT was tested against both an office-based version of FFT and TAU for alcohol-using adolescents recruited from runaway shelters. Both EBFT and FFT were superior to TAU in reducing ASU, though all groups showed comparable improvement in family and adolescent functioning.…”
Section: Ecological Fbtsmentioning
confidence: 99%
“…In the first (Slesnick & Prestopnik, 2009) EBFT was tested against both an office-based version of FFT and TAU for alcohol-using adolescents recruited from runaway shelters. Both EBFT and FFT were superior to TAU in reducing ASU, though all groups showed comparable improvement in family and adolescent functioning.…”
Section: Ecological Fbtsmentioning
confidence: 99%
“…Of the twelve studies included in the systematic review, engagement-related analyses were reported in five studies (Baer et al 2007;Peterson et al 2006;Rotheram-Borus et al 2003;Slesnick and Prestopnik 2009;Slesnick et al 2007). All of these studies were based in the US.…”
Section: Search Results and Description Of Included Studiesmentioning
confidence: 99%
“…According to Rotheram-Borus et al (2003), the number of intervention sessions completed varied across the shelters at which the intervention took place, and, in one shelter, was significantly associated with length of stay at the shelter. Slesnick and Prestopnik (2009) speculate on the role of the intervention location (home vs. office), but this was not empirically examined.…”
Section: Factors Shaping Engagement In Interventions For Street-connementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that once the drinker enters treatment, family-involved treatment is marginally more effective than individual alcoholism treatment. Recent research using family therapy to treat alcoholism are involved Slesnick and Prestopnik (2009), who used two types of family therapy with alcohol-abusing runaway adolescents and compared the outcomes. Their study demonstrated the efficacy of family therapy in treating alcohol-abuse.…”
Section: Distribution Of Abstract Plusmentioning
confidence: 99%